2021
DOI: 10.1002/agj2.20917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrochemically precipitated struvite as a fertilizer‐phosphorus source in flood‐irrigated rice

Abstract: Phosphorus (P) is a major contaminant in many wastewater sources and has gained interest due to the role P has in eutrophication of receiving waters. Recycling P from wastewater as the mineral struvite (MgNH 4 PO 4 • 6H 2 O) could be a promising option to reduce P discharge into receiving waters and could potentially provide an alternative fertilizer-P source for crop production. The objective of this study was to evaluate the effects of two struvite materials (i.e., electrochemically precipitated struvite [EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 17 publications
(73 citation statements)
references
References 94 publications
(125 reference statements)
3
16
0
Order By: Relevance
“…Collectively, and similar to conclusions from Omidire et al. (2021) in rice, results showed that CPST had no substantial negative effects on soybean growth and productivity compared with TSP, thus supporting CPST as a potential alternative fertilizer‐P option for large‐scale soybean production in a wheat–soybean double‐crop system.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Collectively, and similar to conclusions from Omidire et al. (2021) in rice, results showed that CPST had no substantial negative effects on soybean growth and productivity compared with TSP, thus supporting CPST as a potential alternative fertilizer‐P option for large‐scale soybean production in a wheat–soybean double‐crop system.…”
Section: Resultssupporting
confidence: 87%
“…Similar plant growth or tissue-P uptake characteristics have been reported in many studies comparing struvite to other common fertilizer-P sources (Ghosh et al, 1996;Gonzalez-Ponce et al, 2009;Johnston & Richards, 2003;Li & Zhao, 2003;Kern et al, 2008;Massey et al, 2009;Omidire et al, 2021;Thompson, 2013). In contrast to the reported similarities, other studies have shown reduced plant response with…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations